Adaptation of rats to low oxygen pressures - Van Middlesworth, L. (1952)
In a recent publication the author reported on the depressant effect of anoxia on the activity of the thyroid gland of rats. This thyroid depression can be interpreted as an adaptive change that would help adaptation to anoxia. H.E. Himwitch drew attention to information Barrach and others, which indicated that thyroidectomy increases the tolerance of rats to anoxia.